Investigation and analysis on the charging status and standard of pharmacy intravenous admixture service in China - Cao, Jie; Shu, Zhou; Li, Jie; Wang, Dan; Lyu, Yong-Ning; Cai, Xue-Feng (Frontiers in Pharmacology, 2025)
ObjectivesThe charging policy of pharmacy intravenous admixture service (PIVAS) is not merely a minor “billing issue” confined to individual hospitals, but rather a critical component that impacts the safety, efficiency, equity, and long-term sustainability of the national healthcare system. Its implications extend across patients, medical institutions, the pharmaceutical industry, and even the broader public health landscape. To establish a foundation for the national charging standard of intravenous admixture service, this study comprehensively investigated and analyzed the operational costs and current charging policies of PIVAS across 30 provinces in China.MethodsQuestionnaires were distributed through the “Wenjuan Xing” platform from May 6th to 1 July 2022. After data generation and export by the platform, statistical and descriptive analyses of the questionnaire results were conducted using statistical software, including EXCEL, SPSS.ResultsA total of 761 PIVAS surveyed, 91.59% were affiliated with the pharmacy department, while 6.70% belonged to the hospital independent department. Most PIVAS strongly agreed with imposing fees, while most tertiary hospitals agreed that dispensing fees should be categorized based on hospital levels; however, most secondary hospitals disagreed. Approximately 60.58% of PIVAS have implemented a charging system which allows charges after inspection and evaluation. Regarding changes for different drugs nationwide, common drugs had an average charge standard of 4.39 yuan per bag while antibacterial drugs averaged 5.01 yuan per bag. Hazardous drugs had an average charge of 23.17 yuan per bag, whereas parenteral nutrition solutions averaged 38.75 yuan per bag. The annual operating cost of PIVAS in China was approximately RMB 2,098,100, with the integrated operating cost comprising 89.36% of the total, while dispensing cost accounted for only 10.64%. Human costs emerged as the highest annual consumption (74.20%), followed by facility maintenance (4.77%) and equipment acquisition costs (3.44%).ConclusionThe lack of a unified inspection and evaluation standard as well as charging standard in China is currently an urgent issue that needs to be addressed. The existing charging standard falls below the recommended level, thus it is necessary to develop a more reasonable and equitable charging standard that takes into account operational costs. This study can serve as an empirical reference for national medical insurance and health administration authorities in establishing unified regulatory standards and dynamic pricing adjustment mechanisms for PIVAS. It contributes to the transition of PIVAS from “regionally fragmented management” to “nationally standardized operations,” thereby supporting the dual objectives of enhancing healthcare service quality and optimizing the utilization efficiency of medical insurance funds.